What is tongue-tie and does it interfere with breast-feeding? – a brief review - Borowitz, Stephen M. (Frontiers in Pediatrics, 2023)
The most common symptom attributed to ankyloglossia is difficulty breast feeding due to poor latch, inefficient milk extraction and/or maternal nipple pain. During the past two decades, despite a declining birth rate, there has been a dramatic increase in the number of infants diagnosed with and treated for ankyloglossia in the United States, Canada and Australia. Despite a dramatic increase in the diagnosis and treatment of ankyloglossia in these countries, there remains no universally agreed upon definition of ankyloglossia and none of the published scoring systems have been rigorously validated. However ankyloglossia is defined, the majority of infants with ankyloglossia are asymptomatic. Perhaps, infants with ankyloglossia have a greater incidence of difficulty breast feeding. Lingual frenulotomy may decrease maternal pain and at least transiently improve the quality of breast feeding in some infants however no published studies take into account the fact that sucking and feeding are soothing to infants and the observed improvements immediately following frenulotomy may be a response to the pain associated with the procedure rather than a result of the procedure itself. While there are almost certainly some infants in whom tongue-tie interferes with breast-feeding, there is currently no good evidence lingual frenulotomy leads to longer duration of breast-feeding. Frenulotomy appears to be a generally safe procedure however there are reports of serious complications. Finally, there are no studies of long-term outcomes following frenulotomy during infancy and given traditional thinking that the lingual frenulum is a cord of connective tissue tethering the tongue to the floor of the mouth may be incorrect and the frenulum contains motor and sensory branches of the lingual nerve, the procedure may be less benign than previously thought.